Result of the 2016 Oxford Classification Apply in Children with Nephritis Caused by Henoch Schonlein Purpura - Hong Diep, Pho; Tuan Dung, Trinh; Ngoc Thanh, Hoang; Van Dem, Pham; Thu Huong, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 3DO - 10.25073/2588-1132/vnumps.4379, 2022)
Abstract: Henoch Schonlein purpura (Henoch Schonlein purpura-HSP) is a systemic inflammatory vasculitis with IgA deposition causing damage to multiple organ systems in which kidney damage can progress to end-stage renal disease. A retrospective study in 70 children with HSP nephritis ≤ 15 years old who had kidney biopsy at the National Children's Hospital for 5 years (2016-2020) and classified according to the updated 2016 Oxford classification criteria. The result showed that the rates of mesangial hypercellularity (M1), endocapillary proliferation (E1), segmental glomerulosclerosis/adhesion (S1), tubular atrophy/interstitial fibrosis (T1, T2) and crescent (C1, C2) were 34 (48.6%), 32 (45.7%), 43 (61.4%), 3 (4.3% and 0%) and 47 (51.4% and 15.7%). The Oxford classification applied to the histopathological diagnosis of HSP nephritis helps to comprehensively assess the glomerular injury scores (M, E, S, C) and tubules, interstitial tissue (T), thereby treatment orientation and disease prognosis. Keywords: Henoch-Schonlein purpura, HSP nephritis in children, Oxford classification criteria.